Evaluating doses of multi-slice CT in brain examinations using various methods. (31st October 2017) - Lin, Hung-Chih; Lai, Te-Jen; Tseng, Hsien-Chun; Lin, Cheng-Hsun; Tseng, Yen-Ling; Chen, Chien-Yi
Abstract: Purpose: The effective dose (HE ) and organ or tissue equivalent dose (HT ) of a Rando phantom undergoing two brain computed tomography (CT) examination protocols were evaluated using thermoluminescent dosimeters (TLD-100H) and dose length product (DLP) methods. Materials and methods: TLDs were inserted into the correlated positions of an organ or tissue of Rando phantom, such as thyroid, brain, and salivary gland, using (A) axial scan: scanning the maxillae ranging from external auditory meatus to the parietal bone, and (B) helical scan: scanning from the mandible to the parietal bone. CT examinations were performed on a Philips computer tomography (Brilliance CT) at Lukang Christian Hospital. TLDs were measured using a Harshaw 3500 TLD reader. The HT of organ and tissue during the two protocols was discussed. Results and conclusion: HE were calculated using ICRP 60 and 103 at 2.67 ± 0.18 and 1.89 ± 0.23 mSv based on an axial scan, and 4.70 ± 0.38 and 4.39 ± 0.37 mSv based on a helical scan, respectively. In the DLP method, HE was estimated from CTDIvol that was recorded directly from the console display of the CT unit and then calculated using AAPM 96. Finally, experimental results are compared with those in literature. Radiologists should choose and adjust protocols to prevent unnecessary radiation to patients and satisfying the as low as reasonably achievable (ALARA) principle. These findings will be valuable to patients, physicians, radiologists, and the public.